ANALISA KEBIJAKAN PEMERINTAH INDONESIA TERHADAP ANCAMAN KERJA PASCA INFLASI - Wirren Chang; Agnes Doraresta Khatarina Tokan; Dewi; Gladys Christiani; Mardiana Ng; Serina; Wisnu Yuwono (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
The increase in inflation that occurs causes the threat of unemployment in Indonesia. According to the BPS, 4.48 million Indonesians are unemployed in 2022. Cyclical unemployment is unemployment caused by a large-scale economic crisis (inflation), so many companies lay off their workers to reduce the risk of loss in a company. the. The method used in this research is literature study. The literature study method is a method that is carried out by collecting data and documents from references that are in accordance with the author's research. In this study, the authors analyze monetary policy as a government policy that can be used in overcoming the threat of post-inflation unemployment. Monetary policy is one way to reduce unemployment by increasing the money supply and reducing interest rates which will increase investment. The increasing amount of investment will increase job opportunities which in turn will reduce unemployment